Kimberly Perez: capstone - Perez, Kimberly, artist (Colorado State University. Libraries, 2024)
The artist's statement: Kimberly Perez is an adventurous artist that strives to challenge artistic themes and enjoys discovering new styles. While she explores with mediums from painting, to fibers, she always keeps the essence of digital design alive within her work. She gathers inspiration from video games, natural environments, and whimsical fiction. Although she hyper focuses on cleanliness and clarity, she always makes sure to include some spunk to keep the audience captivated.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design